Antifeedant and Antifungal Compounds from Dirca palustris - Murugesan, S.; Ramsewak, R. S.; Mattson, W. J.; Nair, M. G.; Narayanan, C.; Mohan, V. (Indian Forester, 2003)
Wide range of insect pests and fungal pathogens attack seedlings, saplings and trees of economic important viz., Teak, Neem, Bamboo, Eucalyptus and Casuarina. The study highlights those solvent extracts of D. palustris (leather plant) responsible for antifeedant activity against Teak defoliator Hyblaea puera and skeletonizer Eutectona machaeralis. It was tested for fungal toxicity against some forest tree pathogens also.